THE INFLUENCE OF INVESTOR BEHAVIOR ON INVESTMENT DECISIONS WITH PROFIT INFORMATION AS A MODERATING VARIABLE - Manullang, Rizal R.; Pian TA, Suprianus; Maulina, Evaf; Arif Nasution, Abdillah; Nasution, Aulia Arif (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is quantitative research with an exploratory approach related to Investor Behavior, Investment Decisions, and Information Benefits. The data used in this research is of course primary data which is distributed online through a questionnaire containing 5 statement items for 14 questions covering 6 question items for the Investor Behavior variable, 4 question items for the Decision Variable variable, and 4 question items for the Information Profit variable. Researchers analyzed these data using the smart PLS 4.0 analysis tool with the hypothesis below. The result int this research show the Investor Behavior variable have a positive relationship and a significant influence on the Investment Decision variable can be accepted and even justified. This is because the P-Values results are positive and are below the significance level of 0.05, namely 0.002. These results are in line with research . The reason for creating these results, namely Investor Behavior, one of the characteristics is someone, in this case a student who is good at saving, is interested in investment, and has the desire to increase his finances many times over. Apart from this, the second hypothesis in this research can also be proven for the same reason, namely the P-Vlues value which has a positive relationship direction and is below the 0.05 significance level, namely 0.000. Thus the first and second hypotheses in this research can be proven and accepted. Keywords: Investor Behavior, Investor Decision, Profit Information